(untitled) (Research, Society and Development, 2022)
This paper discusses technological innovations in health, highlighting the contributions of nursing in this scenario. It seeks to critically discuss the importance of technological innovations in health, from the professional field of nursing. Therefore, it makes considerations and descriptions about the process and the creative scenario of modern nursing. Then, based on this framework, it outlines a brief overview of inventions and patents in nursing, in order to highlight the main difficulties in registering patents in the professional field of nursing. Finally, it debates the curricular training of nurses with regard to the disciplinary component of technological creations. As for its objectives, this research is classified as exploratory and descriptive, as it seeks to describe the scenario of technological innovations in the field of nursing, thus providing greater familiarity with the aforementioned theme. Regarding its technical procedures, it uses the bibliographic research technique to consult specialized literature, as well as the documental research technique to consult the legislation and other documents relevant to the discussions raised here. Thus, it is presented as a literature review research. It is justified by the almost absence of current research of this nature - considering the last five years - on the contributions of nursing in the process of health innovations, as seen in the databases researched using specific descriptors, namely: technological innovation and nursing; technological innovation and health; nursing and intellectual property.